Hydroxychloroquine Use in Lupus Patients during Pregnancy Is Associated with Longer Pregnancy Duration in Preterm Births. (17th December 2017) - Kroese, S. J.; de Hair, M. J. H.; Limper, M.; Lely, A. T.; van Laar, J. M.; Derksen, R. H. W. M.; Fritsch-Stork, R. D. E.
Abstract : Objective . To investigate the effect of hydroxychloroquine (HCQ) in pregnant women with systemic lupus erythematosus (SLE). Methods . In SLE pregnancies of a single Dutch center (2000–2015), lupus activity and flares before and during pregnancy and postpartum were assessed using the SLE Disease Activity Index (SLEDAI)/SLEPDAI (SLEDAI adjusted for pregnancy). The association between HCQ use and pregnancy outcomes (early spontaneous abortion, fetal death, and preterm and term live birth) was analyzed using generalized estimating equations (GEE) accounting for the occurrence of multiple pregnancies per patient. Analyses were adjusted for antiphospholipid antibody (aPL) status. Results . 110 pregnancies (63 mostly Caucasian patients) were included, of which, in 30, HCQ was used; overall occurrence of flares was low (non-HCQ group: 5 mild (6.4%) and 2 severe (2.6%); HCQ group: 2 mild (6.7%) and no severe flares). The HCQ group showed a trend towards lower dosage of prednisone (OR 0.2 (95% CI 0.0–1.4); p = 0.10 ). Pregnancy outcomes were comparable between groups. Among preterm live births, pregnancy duration was significantly longer in HCQ users (2.4 weeks (95% CI 1.0–3.8; p ≤ 0.001 )). Conclusion . HCQ use was associated with longer pregnancy duration in the vulnerable preterm birth population, underscoring the beneficial effect of HCQ use during pregnancy.